2013
DOI: 10.1152/ajprenal.00507.2012
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone inhibits macrophage infiltration in 5/6 nephrectomized rats

Abstract: Tubulointerstitial macrophage infiltration is a hallmark of chronic kidney disease involved in the progression of renal fibrosis. Pirfenidone is a newly identified antifibrotic drug, the potential mechanism of which remains unclear. The aim of this study was to investigate the effects of pirfenidone on M1/M2 macrophage infiltration in nephrectomized rats. Nephrectomized rats were treated with pirfenidone by gavage for 12 wk. Twenty-four hour urinary protein, N-acetyl-␤-Dglycosaminidase (NAG) activity, systolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 38 publications
3
30
0
1
Order By: Relevance
“…However, the precise anti-fibrosis mechanism of this drug is not clear. Our previous study in the same animal model found that fibronectin was decreased significantly after pirfenidone treatment [21]. The present study successfully demonstrated that pirfenidone improved renal functions and ameliorated tubulointerstitial fibrosis by preventing mitochondrial dysfunction in renal tubular cells.…”
Section: Discussionsupporting
confidence: 74%
“…However, the precise anti-fibrosis mechanism of this drug is not clear. Our previous study in the same animal model found that fibronectin was decreased significantly after pirfenidone treatment [21]. The present study successfully demonstrated that pirfenidone improved renal functions and ameliorated tubulointerstitial fibrosis by preventing mitochondrial dysfunction in renal tubular cells.…”
Section: Discussionsupporting
confidence: 74%
“…Pirfenidone's effects are, in part, mediated via inhibition of TGF-␤1 synthesis (78). In the kidney, the effects of pirfenidone in suppressing renal fibrosis have been shown in several experimental models including diabetic nephropathy, unilateral ureteral obstruction (UUO), and subtotal nephrectomy (9,74,82). An open-label, single-center pilot study demonstrated that pirfenidone significantly slowed renal function decline rate in patients with FSGS, with a median improvement of 25% in patients who have moderate to severe CKD and are already being treated with angiotensin antagonists (11).…”
Section: Anti-tgf-␤ Therapy In Renal Fibrosismentioning
confidence: 99%
“…The compound exerts anti-fibrotic and anti-inflammatory activities in a variety of animal and cell-based models, and its effects are, in part, mediated by inhibition of TGF-β1 synthesis. 37 The effect of pirfenidone in reducing renal fibrosis has been demonstrated in several experimental models including unilateral ureteral obstruction (UUO), 38 subtotal nephrectomy, 39-41 and diabetic nephropathy. 42 The antifibrotic effects of pirfenidone have also been demonstrated in other models of tissue fibrosis such as bleomycin-induced pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%